Risk analysis in theory and practice - Chavas, Jean-Paul. (Amsterdam ; Boston : Elsevier Butterworth-Heinimann, 2004)
Risk Analysis in Theory and Practice presents an analytical framework and illustrates how to use it to investigate economic decisions under risk.
Includes bibliographical references (p. 231-235) and index.
rpm 30/04/13
Loans
Keywords: Uncertainty; Risk; Decision making; Risk-Econometric models-problems and exercises